2018
DOI: 10.1093/jac/dky353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluconazole prophylaxis on Candida fluconazole susceptibility in premature infants

Abstract: Fluconazole prophylaxis decreased Candida albicans and 'non-albicans' Candida colonization and was associated with a slightly higher fluconazole MIC for colonizing Candida isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…14 Kaufman et al furthermore demonstrated a slight increase of the minimal inhibitory concentration (MIC) in Candida strains colonizing neonates admitted in a randomized clinical trial of fluconazole prophylaxis. 15 A slightly different experience had been described by Sarvikivi et al in their NICU in Finland: in a 12-year period, they did not detect any increase of C. glabrata or C. krusei (while using the fluconazole prophylaxis); however, they observed the appearance of resistance in some strains of C. parapsilosis, that were originally sensitive to fluconazole. It is important to notice that this event happened when they extended the prophylaxis to all the neonates admitted to the NICU instead of reserving it to high-risk subgroups such as VLBW or ELBW neonates.…”
Section: Discussionmentioning
confidence: 82%
“…14 Kaufman et al furthermore demonstrated a slight increase of the minimal inhibitory concentration (MIC) in Candida strains colonizing neonates admitted in a randomized clinical trial of fluconazole prophylaxis. 15 A slightly different experience had been described by Sarvikivi et al in their NICU in Finland: in a 12-year period, they did not detect any increase of C. glabrata or C. krusei (while using the fluconazole prophylaxis); however, they observed the appearance of resistance in some strains of C. parapsilosis, that were originally sensitive to fluconazole. It is important to notice that this event happened when they extended the prophylaxis to all the neonates admitted to the NICU instead of reserving it to high-risk subgroups such as VLBW or ELBW neonates.…”
Section: Discussionmentioning
confidence: 82%
“…The incorporation of a loading dose is consistent with previous findings and is often currently used in clinical practice . The MIC of 8 mg/L used in these simulations likely provides a conservative estimate given that the actual MIC values measured during the prophylaxis study were 0.25–1 mg/L . A follow‐up study of Candida susceptibility to fluconazole found that only 4% of isolates were resistant, further supporting the efficacy of fluconazole when using the proposed dosing regimen .…”
Section: Discussionmentioning
confidence: 89%
“…Throughout the prophylaxis study, Candida isolates were collected at study days 0–7, study days 8–28, and study days 29–49 . MIC values were tested using the Clinical and Laboratory Standards Institute method for all positive Candida cultures .…”
Section: Methodsmentioning
confidence: 99%
“…biofilm [ 57 ]; C. krusei possesses an intrinsic resistance to azoles and C. glabrata is less susceptible to them [ 66 ]. Additionally, the emerging resistance to this group of drugs among isolates of Candida spp., especially C. auris , C. parapsilosis and C. tropicalis is currently observed [ 54 , 70 ] as a consequence of the massive preventive application of fluconazole [ 71 , 72 ] and common use of agricultural fungicides, structurally similar to azoles [ 73 ]. The resistance relies on the mutations or overexpression of ERG11 and ERG3 genes, which lead to increased tolerance to methylated sterols and overexpression of drug-efflux pumps that transport azoles outside of the fungal cell [ 65 , 67 ].…”
Section: Current Methods For Treatment and Management Of Superficimentioning
confidence: 99%